Battery Inspection Of 380 kWp Off-Grid Solar Power Plant (PLTS) on Mules Island, East Nusa Tenggara - Falah, Aap Syamsul; Fauziah, Dini; Sujana, Tri Jajang (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2024)
Off-Grid Solar Power Plant is a power generation system that uses solar energy. Battery maintenance is important in maintaining the stability of this system. This research focuses on battery maintenance by checking in a keHua monitoring tool for 389 battery units and monitoring the battery graph for 30 days. The results showed that there were 15 batteries that experienced a voltage drop below 1.83 Volts. The voltage drop occurred between 21:00 and 00:00, so the batteries were considered damaged. The battery capacity requirement on Mules Island, East Nusa Teggara increased from 778 kWh in 2019 to 936.9 kWh in 2021. To maintain the reliability of the Off-Grid Solar PV system on Mules Island, it is necessary to replace 15 damaged battery units and add a new battery capacity of at least 157.9 kWh so that the system can run well and customers can enjoy electricity for 24 hours as at the beginning of the implementation.